2013
DOI: 10.5861/ijrsll.2013.624
|View full text |Cite
|
Sign up to set email alerts
|

The development of speaking fluency: The 4/3/2 technique for the EFL learners in China

Abstract: EFL teaching is gradually changed from a traditional grammar-based model to a communicative language teaching approach in China. So, there is a variety of methodologies to help the Chinese EFL learners to practice their speaking skills. Lack of speaking fluency practice, sometimes, is not sufficient to maintain a communicative task in EFL class. This paper examines previous studies and researches in fluency development: to point out the importance of speaking fluency; to outline a 4/3/2 method adapting in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Previous research found that lecturers should frequently provide fluency activities for successful language learning, especially when English is regarded as a foreign language [5]. The importance of speaking fluency in establishing communication in the EFL classroom was also emphasized in the finding of a research result [6]. This research found that fluency also brought advantages in improving the quality of speaking in a real-life context.…”
Section: Introductionmentioning
confidence: 84%
“…Previous research found that lecturers should frequently provide fluency activities for successful language learning, especially when English is regarded as a foreign language [5]. The importance of speaking fluency in establishing communication in the EFL classroom was also emphasized in the finding of a research result [6]. This research found that fluency also brought advantages in improving the quality of speaking in a real-life context.…”
Section: Introductionmentioning
confidence: 84%
“…For instance, speech rate is regarded as in important predictor of speech fluency and is defined as the average number of syllables articulated per minute (Ejzenberg, 2000;Namaziandost, Abdi Saray, & Rahimi Esfahani, 2018). It is interesting to know that there are a lot of other definitions for speaking fluency (Yingjie, 2014). According to Hartmann and Stork (1976), fluent speaker is a speaker who is capable of using the appropriate structures of a language at standard speed, which means natural speaking while the focus is on the delivery meaning rather than the form or structure of a language.…”
Section: )mentioning
confidence: 99%
“…This continues until the learner is happy with the recording. This technique can involve planning and encourages repetition of the setting of a quality-based goal (Yingjie, 2014). Boud and Walker (1992) provided a way of conceptualizing experience-based learning which considers the personal foundation of experience of learners, their intent and their interaction with a learning milieu.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, another resent study of developing speaking fluency by EFL Chinese university learners was also conducted. Through a three-month case study of oral fluency developments for eleven participants, Yang (2013) found that developing speech fluency can be "a trainable skill" in terms of enhancing the speed rate of speaking, reducing hesitations disfluency (p. 68). Similarly, in their study of fluency in the speech of second language learners, Kormos and Dénes (2004) mainly attempted to investigate what variables can predict the perception of fluency other than the traditional measures as "accuracy and lexical diversity."…”
Section: Speech Fluency In the Perceptions Of Native And Nonnative Spmentioning
confidence: 99%